An Elective Course in Information Mastery - Longyhore, Daniel (American Journal of Pharmaceutical Education, 2011)
OBJECTIVE: To design and implement an elective course in information mastery and assess its impact on students' ability to identify information needs and formulate clinically relevant, evidence-based answers. DESIGN: A semester-long (15-week) elective course was offered to third-year (P3) doctor of pharmacy (PharmD) students that outlined the necessary knowledge and skills for using information mastery in evidence-based practice. ASSESSMENT: Results of a pre- and postcourse survey instrument demonstrated an increase in students' knowledge of information mastery and confidence in and familiarity with the practice of evidence-based medicine in pharmacy. Students who had completed the elective were able to provide higher quality search strategies and evidence-based answers to a clinical question than other P3 students, and P4 students who did not participate in the elective. CONCLUSION: An elective course in information mastery improved students' knowledge and understanding of information mastery as it pertains to practicing evidence-based medicine.